The Relationship of Giving Non Material Incentive by Principal and Work Commitment With Teacher Performance - Anisah Anisah; Yuskal Kusman; Tia Ayu Ningrum (Journal of Educational and Learning Studies, 2018)
The background of the research because there is poor performance of teachers. And the purpose of this research iss to see the relationship between non material incentive and work commitment with teacher performance. This research is a correlational quantitative research. The result of data analysis showes 1) The performance of teachers is in good category with achievement level 78,5%; 2) Non material incentive is in good category with achievement level 75,6%, 3) Commitment work is in good category with achievement level 72%, 4) There is significant relation between giving non material incentive and work commitment with teacher performance. Based on the calculation results of correlation test between non-material incentive variable with teacher performance is obtained count equal to 0.248 while table is 0,235. Variable of non material incentive with work commitment variable is obtained count equal to 0,426 while table is 0,235. Work commitment variable with teacher performance is obtained count equal to 0,314 while table is 0,235. And the relation of giving non-material incentive and work commitment with teacher performance is obtained count  0.338 while table is 0,235.  So that, there is relation  between giving non material incentive and work commitment with teacher performance.